Avoiding Misunderstandings About the Emergence and Position of Grundnorm as a Source of Law - Samekto, F.X. Adji; Fatharani, Yasyifa (LAW REFORM, 2025)
Immanuel Kant's teachings on the stages of human knowledge development regarding the universe became the foundation for Hans Kelsen's renowned legal theory, namely Grundnorm. According to Kelsen, Grundnorm exists at the rational-practical stage of each individual, is a priori, and has never been formalized through a constitutional process. However, law students often have a simplistic understanding of Grundnorm, particularly in constitutional law studies.The discussion below falls within the scope of legal positivism, employing a juridical-philosophical approach. Grundnorm is frequently reduced to a mere issue of consistency, where lower regulations must not contradict higher regulations. No further explanation is provided, apart from the assertion that a legal regulation is effective only if consistency between lower and higher rules is maintained. This oversimplified explanation can be misleading, as it fails to convey the essence of Grundnorm theory to law students. Based on this analysis, it can be concluded that, according to Hans Kelsen’s teachings, Grundnorm is the highest source of legal norms, accepted as a necessity by individuals through their free will. Grundnorm, as an imperative-categorical basic norm, can be transformed into legal principles if it has been widely accepted by society.